Community Participation in Village Development and Empowerment Study in Timbal Village, West Bacan District South Halmahera Regency - Moch Suwa Ahdiyansyah; Ali Lating; Syarifuddin Usman (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
Abstrac Community participation in village development and empowerment is very important for a village, because community participation is the active and effective involvement of the community in the decision-making and development processes that affect their lives. This is a process in which the community has the opportunity to provide input, influence decisions, and take part in the implementation and monitoring of development projects. Community participation has several benefits, such as increasing transparency and accountability in the decision-making process, ensuring that the results taken take into account the interests and needs of the community, and helping to create more inclusive and sustainable solutions. Community participation can be done through various means, such as public consultations, surveys, group discussions, deliberations, and so on. This can happen at various levels, from local to national. The aim of this research is to determine community participation and factors that hinder community participation in development in Tembal Village, South Bacan District, South Halmahera Regency. The type of research used in this research is descriptive qualitative. Meanwhile, the data collection techniques used in this research are observation, interviews, and documentation. As well as using model data analysis techniques, the Miles and Huberman model, namely data reduction, data display and conclusion drawing/verification. Based on the research results, it shows that community participation in village development and empowerment can be seen from participation in decision making, participation in implementation, participation in taking benefits, participation in evaluation.